2014
DOI: 10.12816/0023982
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Disinfectants on the Color of a Porcelain Shade Guide

Abstract: Abstract:Objective: To evaluate the effect of long term utilization of chemical disinfectants on the color of porcelain shade guides.Methodology: three chemical disinfectants were used in this study: Minuten spray, Lysol ICQuaternary Disinfectant Cleaner (QDC), and Lysol IC Ready to Use Disinfectant Cleaner (RDC). Simulation of disinfecting cycles for one year, two years, and three years were done on Vita 3D master shade guide. Color differences were determined by visual inspection and analyzing ΔE.Results: ΔE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These findings were constant with the results of the current study in the disinfectant group. [23] The amount of ΔE was under the perceptible level (ΔE = 1) and the clinically acceptable level (ΔE = 3.7). [23] In the current study, the variation was greater than the perceptible level and lower than the clinically acceptable level in the test specimens, while it was lower than perceptible level as well as the clinically acceptable level in the control specimens.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were constant with the results of the current study in the disinfectant group. [23] The amount of ΔE was under the perceptible level (ΔE = 1) and the clinically acceptable level (ΔE = 3.7). [23] In the current study, the variation was greater than the perceptible level and lower than the clinically acceptable level in the test specimens, while it was lower than perceptible level as well as the clinically acceptable level in the control specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies explored issues associated with visual shade matching 2,7,11,[13][14][15] and the efficacy of the spectrophotometer extensively. Previous studies explored issues associated with visual shade matching 2,7,11,[13][14][15] and the efficacy of the spectrophotometer extensively.…”
Section: All Participants' Satisfaction With Shade-matching Outcomementioning
confidence: 99%
“…The patients included in our study reported high satisfaction ratings, indicating that subjective visual shade-matching selection with a shade guide can still be a viable option to produce definitive restoration with clinically acceptable esthetic outcome. Previous studies explored issues associated with visual shade matching 2,7,11,[13][14][15] and the efficacy of the spectrophotometer extensively. 16,[30][31][32][33][34] Our study explored different components of the shade-matching outcome from subjective visual shade-matching selection with a shade guide and can potentially provide future direction of shade-matching education in dental schools.…”
Section: All Participants' Satisfaction With Shade-matching Outcomementioning
confidence: 99%
See 2 more Smart Citations